Comparative assessment of the interfacial soft and hard tissues investing implants and natural teeth in the macaque mandible - Siar, C.H.; Toh, C.G.; Romanos, G.E.; Ng, K.H. (2015)
Objectives The aim of this study was to conduct a comparative qualitative and quantitative assessment of the interfacial soft and hard tissues investing implants and natural teeth.